The cyanobacterial ribosomal-associated protein LrtA is involved in post-stress survival in Synechocystis sp. PCC 6803 - Galmozzi, Carla; Florencio, Francisco J.; Muro-Pastor, M. Isabel (PLOS ONE, 2016)
A light-repressed transcript encodes the LrtA protein in cyanobacteria. We show that half-life of lrtA transcript from Synechocystis sp. PCC 6803 is higher in dark-treated cells as compared to light-grown cells, suggesting post-transcriptional control of lrtA expression. The lrtA 5´ untranslated leader region is involved in that darkness-dependent regulation. We also found that Synechocystis sp. PCC 6803 LrtA is a ribosome-associated protein present in both 30S and 70S ribosomal particles. In order to investigate the function of this protein we have constructed a deletion mutant of the lrtA gene. Cells lacking LrtA (∆lrtA) had significantly lower amount of 70S particles and a greater amount of 30S and 50S particles, suggesting a role of LrtA in stabilizing 70S particles. Synechocystis strains with different amounts of LrtA protein: wild-type, ∆lrtA, and LrtAS (overexpressing lrtA) showed no differences in their growth rate under standard laboratory conditions. However, a clear LrtA dose-dependent effect was observed in the presence of the antibiotic tylosin, being the LrtAS strains the most sensitive. Similar results were obtained under hyperosmotic stress caused by sorbitol. Conversely, after prolonged periods of starvation, ∆lrtA strains were delayed in their growth with respect to the wild-type and the LrtAS strains. A positive role of LrtA protein in post-stress survival is proposed.
Gesehen am 06.05.2020